LEARNING THE FUNDAMENTALS OF OBJECT-ORIENTED PROGRAMMING WITH VISUAL C # (Journal of Information Technologies in Education (ITE), 2020)
The article provides guidelines for studying the discipline "Object-Oriented Programming" for the training of specialists of the first (bachelor's) level of higher education in the field of knowledge 01 "Education" specialty 014 "Secondary education (computer science)" educational program (computer science, mathematics). This discipline plays a particularly important role in the training of computer science teachers, because the field of computer program development using the latest technologies, which includes object-oriented programming, is an important component of scientific and technological progress.Students are invited to consider the basic features of object-oriented programming and the principles of a visual approach to software design in an integrated environment Visual Studio.Net using Visual C#. The choice of Visual Studio.Net is due to the fact that the version of Visual Studio.Net Community is a free full-featured version, which differs from the professional only slightly limited features.The article considers the method of studying the basics and principles of object-oriented programming by demonstrating typical examples in lectures and consolidating the studied material in laboratory work. The examples are selected in such a way that it is possible to demonstrate the features of data input and output in the Visual C# visual programming environment, event programming, file processing, implementation of encapsulation, inheritance and polymorphism mechanisms. Simultaneously with the demonstration of the implementation of typical examples, the required properties of the control elements used in the project implementation are studied. By performing laboratory work, students consolidate the knowledge gained in lectures and acquire practical skills of project development using Visual C#. The laboratory work ends with the creation of a multi-window project, which represents a computer training system for studying computational methods. The creation of such a project allows students to consolidate the theoretical knowledge and practical skills of program development and demonstrates the use of interdisciplinary links in the educational process.
Keywords: computer science teacher, object-oriented programming, Visual C# visual programming environment